Introduction to “Refugee Crises Disclosed: Intersections between Media, Communication and Forced Migration Processes” - Tsagkroni, Vasiliki (2019)
This editorial serves as an introduction to the Media and Communication thematic issue on “Refugee Crises Disclosed: Intersections between Media, Communication and Forced Migration Processes”. This thematic issue presents an integrated look at forced migration through the spectrum of media studies and communication sciences. The eleven articles in this volume offer a comparative research approach on different focuses that involve cross-national, cross-disciplinary, cross-cultural frameworks, as well as multi-actor perspectives and methodologies. Altogether, the contributions featured in this thematic issue offer inspiring insights and promote innovative research on the way we perceive implications of media and communication in the field of migration. To conclude, a reflection on the presented research is also included.